Developing and Testing Inquiry-Based E-Modules for Learning Plant Structure and Tissues in Senior High Schools - Muhibbuddin Muhibbuddin; Wiwit Artika; Samsul Kamal; Sajid Ali Yousuf Zai (Jurnal Ilmiah Peuradeun, 2026)
Plant structure and tissues constitute fundamental topics in senior high school biology; however, students’ learning outcomes in this area remain unsatisfactory due to conceptual complexity and limited instructional support. To address this issue, this study aimed to develop and examine the effectiveness of an inquiry-based interactive e-module for learning plant structure and tissues at the senior high school level. The study employed a Research and Development approach using Thiagarajan’s 4-D model, which consists of the define, design, develop, and disseminate stages. The dissemination stage was conducted through an experimental method using a pretest–posttest control group design. Data were collected through expert validation sheets, questionnaires, observations, and learning outcome tests, and analyzed using descriptive techniques and an independent samples t-test. The results indicate that the developed inquiry-based e-module is pedagogically feasible and statistically effective in improving students’ learning outcomes compared to conventional instruction. The e-module can function both as an independent learning resource and as an instructional support within classroom and online learning environments. This study contributes empirical evidence that integrating inquiry-based pedagogy into digital learning modules enhances conceptual understanding and supports more active and independent learning in biology education.